Entry into work following childbirth among mothers in Norway. Recent trends and variation - Marit Rønsen; Ragni Hege Kitterød (Statistics Norway, Research Department, 2012)
Universal parental leaves with job protection and earnings compensation increase women's attachment to the labour market, but very long leaves may have negative consequences both at the individual and the societal level. Some scholars have therefore argued that generous family-friendly policies in the Nordic countries have been counterproductive in achieving one of the main goals, gender equality. In this paper we ask whether it is possible to offset the potential negative effects on women's labour supply of long parental leaves by policies targeted especially at the father, and policies making formal day care cheaper and more easily available for parents. Norway is an interesting case in this respect, since all recent extensions in the parental leave scheme have been reserved for fathers and at the same time there has been a vast expansion of the day-care sector combined with reduced parental payment. Using panel data from 1996-2010, we find that Norwegian mothers did indeed enter work faster after childbirth in the late 2000s than about a decade earlier. This suggests that the latest initiatives have contributed to a shortening of women's employment interruptions and a more equal division of paid and unpaid work among parents.
Keywords: J13; J16; J22; J24; I38; 330; Female labour supply; childbirth; parental leave; gender equality